(untitled) (Orthodontic Journal of Nepal, 2021)
Introduction: Many reference planes are being used to determine prominence of upper and lower lip for orthognathic face profile. E-line and S-line are being used to determine lip position in local popuation of Multan city of Pakistan. Materials and Method: Execution of present study was done in Nishtar Institute of Dentistry, Multan during the period of November 2019-March 2020. 300 (112 Males and 188 Females) subjects were selected for this study from all provinces of Pakistan. Their radiographic records (Lateral cephalograms) were taken from radiographic department of related institution. Acetate matte sheets were used to construct reference planes by using 3H pencil. Steiner’s E-line and Rickett’s S-line were used to find Upper and Lower lip position from these reference lines. SPSS was used to analyze data after applying independent t-test. Result: Mean Upper and lower lip position from E- line was -1.74mm & -0.33mm and from S-line was 0.82mm and 1.47mm Conclusion: Cephalometric lip morphology assessment in Multan, Pakistani adults by using Steiner’s and Ricketts reference planes on lateral cephalogram is slightly different as compare to other populations